Sap flow dynamics of co-occurring trees in response to seasonal droughts in a subtropical climate - Tang, Jiaqi; Ding, Zhiqiang; Wang, Guohua; Wang, Yanfang (Frontiers in Ecology and Evolution, 2025)
IntroductionClimate change and extreme rainfall events pose significant challenges to water use strategies for forest species in subtropical regions. Increased degrees of drought and significant seasonal precipitation differences in recent decades in Yunnan Province, China, have exposed forests to high mortality rates. Therefore, there is an urgent need to understand the water use strategies of plants to help develop relevant forest conservation measures in this region.MethodsIn this study, we selected three co-occurring woody species (Pinus yunnanensis, Keteleeria evelyniana, and Castanopsis delavayi). We continuously monitored their sap flow and water potential, as well as environmental factors, to reveal plant water use strategies and to determine how water use strategies relate to environmental factors and vegetation traits.ResultsThe results of this study revealed that seasonal water use strategies of plants were significantly different (P<0.01), with Js lower in the dry season than in the wet season, while the Js/Js,n was significantly higher in the dry season. Plant water use responded to seasonal environmental factors similarly. SWC was the main limiting factor for Jsin the dry season, and there was a positive correlation between Js,n and VPD; when SWC was sufficient in the wet season, VPD and PAR were the main factors on Js, and there was a negative correlation between Js,n and VPD. In addition, Js,n during the dry season consisted of En and Re, and En accounted for a high percentage (more than 60%). Finally, there are differences in the water use strategies of different species, with Pinus having less tight stomatal control in the dry season, possibly related to its deeper roots and relatively smaller leaf area.DiscussionThese findings on the water use strategies and environmental responses of different species complement our knowledge of survival strategies in subtropical forests and provide valuable advice for forest management.